2015
DOI: 10.1038/nrurol.2015.168
|View full text |Cite
|
Sign up to set email alerts
|

Novel targets in altered tumour metabolism in kidney cancer

Abstract: Refers to Wettersten, H. I. et al. Grade-dependent metabolic reprogramming in kidney cancer revealed by combined proteomics and metabolomics analysis. Cancer Res. http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Studies showed that the initiation and execution of ferroptosis are tightly linked to the metabolism of amino acid, iron, and polyunsaturated fatty acid [25]. As it happens, metabolic reprogramming is the prominent feature of RCC, such that this cancer is labeled a metabolic disease [26]. Therefore, it is legitimate to assume that RCC possesses superior sensitivity to ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the initiation and execution of ferroptosis are tightly linked to the metabolism of amino acid, iron, and polyunsaturated fatty acid [25]. As it happens, metabolic reprogramming is the prominent feature of RCC, such that this cancer is labeled a metabolic disease [26]. Therefore, it is legitimate to assume that RCC possesses superior sensitivity to ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most profound increases is that of Ndufa4l2, a mitochondrial protein shown to be required for proliferation and colony formation in kidney cancer cell lines ( 10 , 15 ). Importantly, Ndufa4l2 is also elevated in human ccRCC ( 15 , 38 ), and this high expression in cancer makes NDUFA4L2 a promising target for therapeutic approaches. In the present study, we decreased Ndufa4l2 expression in our TRACK ccRCC animal model to evaluate the effects of targeting Ndufa4l2.…”
Section: Discussionmentioning
confidence: 99%
“…cancer cell lines (10,15). Importantly, Ndufa4l2 is also elevated in human ccRCC (15,38), and this high expression in cancer makes NDUFA4L2 a promising target for therapeutic approaches. In the present study, we decreased Ndufa4l2 expression in our TRACK ccRCC animal model to evaluate the effects of targeting Ndufa4l2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Warburg effect (aerobic glycolysis), arginine synthetic abnormalities (caused by arginosuccinate synthetase-1 deficiency), and glutamine pathway reprogramming are all pronounced in RCC. The recent elucidation of the metabolic abnormalities that occur in RCC 10,11 (Figure 1) is not only useful for understanding how this tumor can be so difficult to treat, but also, these data turn out to be a gold mine for therapeutic exploration. Indeed, targeted therapy using pathwayspecific inhibitors (which in some cases, are compounds that were discarded after their discovery) would show high specificity with fewer adverse effects; such an approach will be discussed below.…”
mentioning
confidence: 99%